Effect of two-stage reaction sintering technique on phase formation, microstructure and dielectric properties of 0.93Pb(Zn 1/3Nb 2/3)O3-0.07BaTiO3ceramics - P. Pakawanit (2018)
Influences of a combination between the two-stage sintering and the reaction sintering techniques on phase formation, microstructure and dielectric properties of relaxor perovskite 0.93Pb(Zn1/3Nb2/3)O3-0.07BaTiO3or 0.93PZN-0.07BT ceramics were determined via X-ray diffraction, scanning electron microscopy and dielectric measurement techniques, respectively. Under suitable two-stage reaction sintering schemes, it was found that dense and pure perovskite 0.93PZN-0.07BT ceramics with fine grain size can be successfully achieved with better dielectric properties than those of ceramics from single-stage reaction sintering. © 2013 Copyright Taylor and Francis Group, LLC.